2018
DOI: 10.1155/2018/2767410
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Extra Space as a Tool for the Top-Down Approach

Abstract: The top-down approach for the 6-dimensional space has been elaborated. The connection between the cosmological constant and the extra space metric has been obtained. The metric can be found with the necessary accuracy. It is shown that descent from high energies to the low ones leads to the quantum corrections which influence weakly the metric of extra space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The results of numerical calculation of equations (7), (8) The numerical values of H 1 and H 2 coincide with those found from the (13,14,15) or (19), (20) In this section we have shown that the behavior of the extra spaces depends on initial conditions. We have found out promising conditions and the Lagrangian parameters for which one of the extra spaces remains small while the other expands quickly.…”
Section: The Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…The results of numerical calculation of equations (7), (8) The numerical values of H 1 and H 2 coincide with those found from the (13,14,15) or (19), (20) In this section we have shown that the behavior of the extra spaces depends on initial conditions. We have found out promising conditions and the Lagrangian parameters for which one of the extra spaces remains small while the other expands quickly.…”
Section: The Modelsupporting
confidence: 78%
“…Second, the inclusion of extra dimensions is of particular interest because the idea of extra space is widely used in modern research. They shed light to such issues as the grand unification [10,11], neutrino mass [12], the cosmological constant problem [13][14][15] and so on. In this regard, the immediately aroused question is: why specific number of dimensions are asymptotically compact and stable while others expand [16][17][18]?…”
Section: Introductionmentioning
confidence: 99%
“…The compact extra-dimensional metric could play a crucial role in the physical parameter values such as particle masses and the relevant coupling constants [8]. The nuclear reaction rates inside such domains, and hence the final chemical content and temperature, could differ from the conditions in the surrounding space.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of this problem is aggravated by the inclusion of extra dimensions. The latter is of particular interest because the concept of extra dimensions is widely used in modern research dealing with problems such as grand unification [4,5], the cosmological constant problem [6][7][8], etc.…”
Section: Introductionmentioning
confidence: 99%
“…a e-mail: kb20@yandex.ru b e-mail: arkady_popov@mail.ru c e-mail: sergeirubin@list.ru (corresponding author) In this paper, we study the possible influence of a matter field on the metric of extra dimensions. Previous results concerning multidimensional gravity with 4D Minkowski factor space are published in [13][14][15][16][17], where the importance of inhomogeneous extra dimensions was discussed. In particular, the scalar field localization on deformed extra space.…”
Section: Introductionmentioning
confidence: 99%